2002
DOI: 10.1093/oxfordjournals.molbev.a004012
|View full text |Cite
|
Sign up to set email alerts
|

Serpins in Prokaryotes

Abstract: Members of the serpin (serine proteinase inhibitor) superfamily have been identified in higher multicellular eukaryotes (plants and animals) and viruses but not in bacteria, archaea, or fungi. Thus, the ancestral serpin and the origin of the serpin inhibitory mechanism remain obscure. In this study we characterize 12 serpin-like sequences in the genomes of prokaryotic organisms, extending this protein family to all major branches of life. Notably, these organisms live in dramatically different environments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
140
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 47 publications
3
140
0
4
Order By: Relevance
“…At the core of this mechanism is a hydrogen-bonding network which (in ATIII) chiefly involves His369 on s5A and Asn217 on s3A, together with Ser79 and Ser82. A sequence alignment of 219 serpin sequences (Irving et al, 2000) revealed that these four positions are highly conserved, with the above-mentioned side chains present in 78, 85, 93 and 72% of cases, respectively. The functional significance of the shutter region is underscored by the discovery of naturally occurring mutations of these residues that lead to dysfunction and disease.…”
Section: Shutter Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the core of this mechanism is a hydrogen-bonding network which (in ATIII) chiefly involves His369 on s5A and Asn217 on s3A, together with Ser79 and Ser82. A sequence alignment of 219 serpin sequences (Irving et al, 2000) revealed that these four positions are highly conserved, with the above-mentioned side chains present in 78, 85, 93 and 72% of cases, respectively. The functional significance of the shutter region is underscored by the discovery of naturally occurring mutations of these residues that lead to dysfunction and disease.…”
Section: Shutter Regionmentioning
confidence: 99%
“…In contrast to canonical protease inhibitors, serpins employ a unique conformational mechanism for inactivation of their target protease (Farady & Craik, 2010). A comprehensive phylogenetic analysis of several hundred serpin sequences resulted in a classification into 16 clades; remarkably, the invertebrate members are typically arranged according to speciation (with schistosome serpins forming clade m), while the vertebrate proteins group into diverse clusters (Irving et al, 2000). Although most serpins are inhibitors of serine or cysteine proteases, several members have adopted different functions, acting, for example, as hormone transporters or molecular chaperones.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Serpins function as intracellular or extracellular regulators of a wide range of physiological processes such as complement activation, blood coagulation and apoptosis. Within the vertebrate immune system, they control proteases of the classical and innate complement systems, and are also potent inhibitors of many leukocyte granule proteases.…”
mentioning
confidence: 99%
“…Serpins have been identified in animals, plants, insects, and certain viruses (1,2). More recently, serpins have been detected in prokaryotes (3). A search of genome data bases provides evidence for Ļ¾500 serpins that are grouped into 17 clades (plus Ļ¾10 unclassified orphans) based upon phylogenetic relationships (4).…”
mentioning
confidence: 99%